2007
DOI: 10.1007/s12038-007-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

The Kdp-ATPase system and its regulation

Abstract: K+, the dominant intracellular cation, is required for various physiological processes like turgor homeostasis, pH regulation etc. Bacterial cells have evolved many diverse K+ transporters to maintain the desired concentration of internal K+. In E.coli, the KdpATPase (comprising of the KdpFABC complex), encoded by the kdpFABC operon, is an inducible high-affinity K+ transporter that is synthesised under conditions of severe K+ limitation or osmotic upshift. The E.coli kdp expression is transcriptionally regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
106
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 64 publications
(64 reference statements)
3
106
1
1
Order By: Relevance
“…The MESSAGE 2 transcriptomic results suggest a response to what is felt by the cell as possibly an osmotic stress. Indeed, together with the gene coding for the biosynthesis of the osmoprotectant trehalose synthesis, two membrane-based osmosensors, the mechanosensitive channel MscS and, to a lesser extent, the two-component sensor kinase KdpD as well as a potassium efflux protein were differentially expressed in the MESSAGE 2 space samples (Wood, 1999;Ballal et al, 2007;Gunasekera et al, 2008;Hurst et al, 2008). During a hypo-osmotic shock, that is, sudden reduction of the external osmolarity, induction of a mechanosensitive channel could act as an emergency safety valve (reviewed in Booth et al, 2007) and decreasing potassium influx (down-regulation Kdp-system) and increasing potassium efflux would help to adapt to this hypo-osmotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The MESSAGE 2 transcriptomic results suggest a response to what is felt by the cell as possibly an osmotic stress. Indeed, together with the gene coding for the biosynthesis of the osmoprotectant trehalose synthesis, two membrane-based osmosensors, the mechanosensitive channel MscS and, to a lesser extent, the two-component sensor kinase KdpD as well as a potassium efflux protein were differentially expressed in the MESSAGE 2 space samples (Wood, 1999;Ballal et al, 2007;Gunasekera et al, 2008;Hurst et al, 2008). During a hypo-osmotic shock, that is, sudden reduction of the external osmolarity, induction of a mechanosensitive channel could act as an emergency safety valve (reviewed in Booth et al, 2007) and decreasing potassium influx (down-regulation Kdp-system) and increasing potassium efflux would help to adapt to this hypo-osmotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The KdpDE two-component system was first characterized in Escherichia coli, in which proteins KdpD and KdpE regulate the production of the high-affinity K ϩ transporter KdpATPase (6,19,38,40). In E. coli, Kdp-ATPase is an efficient K ϩ -scavenging system that is expressed when cells are subjected to extreme K ϩ limitation or osmotic upshock and other low-affinity K ϩ transporters cannot meet the cellular requirements for K ϩ (2,4,18,26,27,29).…”
mentioning
confidence: 99%
“…A BLAST search of Kdp protein sequences shows that the Kdp-ATPase system is widely distributed among Gram-negative bacteria (e.g., E. coli, Salmonella enterica serovar Typhimurium LT2, and Clostridium acetobutylicum) and Gram-positive bacteria (e.g., Bacillus cereus E33L, Alicyclobacillus acidocaldarius, and Mycobacterium tuberculosis). In distantly related bacteria, the ordering of the kdpA, kdpB, and kdpC genes is relatively fixed, but the kdpDE genes show different arrangements (6,44,52). In S. aureus, the organization of the kdpFABC operon is similar to that of E. coli, but the kdpDE genes are arranged in a reverse orientation upstream of the kdpA gene.…”
mentioning
confidence: 99%
“…The two sets in M. boonei and one set of Kdp operons in M. palustris likely allow both organisms to overcome low K + concentrations present in oligotrophic and minerotrophic peats. Kdp has a high affinity for K + (K m = 2 μM in Escherichia coli K-12, with 37-63% protein identity to Kdp subunits of M. boonei and M. palustris) and has been shown to concentrate K + in the cytoplasm when extracellular concentrations were as low as 50 nM (Ballal et al, 2007). Our analyses of gene flow dynamics indicated that Kdp was likely acquired subsequent to the divergence of the Methanoregulaceae family, in which the presence of Kdp operons in two peat-dwelling strains, M. boonei and M. palustris, and its absence in two bioreactor-dwelling ones, Methanoregula formicica and M. tarda, suggest that peatlands likely favor methanogens that acquired Kdp.…”
Section: Discussionmentioning
confidence: 99%